2007
DOI: 10.1007/s10152-007-0065-8
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive cycle, condition index and biochemical composition of the horse-bearded mussel Modiolus barbatus

Abstract: The horse-bearded mussel Modiolus barbatus (Linneus, 1758) is an important edible bivalve in the Adriatic Sea; its population is especially large in the Mali Ston Bay area, where the species is present at depths up to 8 m. In order to assess the sustainable exploitation rate for this species, as well as to estimate its potential capacity for a sustainable aquaculture production, we determined the species' reproductive cycle along with its nutrient storage strategy, employing histological and biochemical method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 21 publications
4
23
0
1
Order By: Relevance
“…In this study, an exception was a mean condition index value obtained for individuals collected in April, while the highest MGI values for males and females were obtained in June and July, respectively. A similar trend has been observed for Modiolus barbatus (Linnaeus, 1758), with the highest mean monthly condition index being recorded in May and the highest MGI occurring a few months later in August (Mladineo et al 2007). Villalejo-Fuerte et al (1995) noted that variations in G. gigantea condition index seemed to be influenced by gametogenic development, in accordance with our results.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, an exception was a mean condition index value obtained for individuals collected in April, while the highest MGI values for males and females were obtained in June and July, respectively. A similar trend has been observed for Modiolus barbatus (Linnaeus, 1758), with the highest mean monthly condition index being recorded in May and the highest MGI occurring a few months later in August (Mladineo et al 2007). Villalejo-Fuerte et al (1995) noted that variations in G. gigantea condition index seemed to be influenced by gametogenic development, in accordance with our results.…”
Section: Discussionsupporting
confidence: 92%
“…However, Mladineo et al (2007) reported that the use of stored protein as an energy source is widely dependant on the availability of the other sources such as carbohydrates and lipids, being lower when these other sources are used at higher levels, and vice versa. According to Whyte et al (1990), protein was more efficient than carbohydrate as the main contributor of energy in lean times and fed the oysters during the winter months, when food was scarce.…”
Section: Discussionmentioning
confidence: 99%
“…As reported above, early and late stages of gametogenesis were found between March and May, and spawning peaked from June until August (Mladineo et al 2007). Reproductive activity of Modiolus barbatus results in the depletion of carbohydrates and lipids such that gametogenesis may rely, for the most part, directly on the energy of ingested food (Mladineo et al 2007). Consequently, M. barbatus has to face both the reduction in food and the gradual elevation of ambient temperature from spring to summer.…”
Section: Discussionmentioning
confidence: 84%
“…The period between January and February is characterized by sexual repose in Modiolus barbatus. Early and late stages of gametogenesis were found between March and May, and spawning peaked from June until August (Mladineo et al 2007). …”
Section: Discussionmentioning
confidence: 99%